Use of artificial perches for wild birds in a degraded area in southern Brazil - Hofstätter, Mathias; Mariano, Cristina Jardim Cezar; Chemin, Augusto Pretto; Orlandi, Carla Roberta; Bianchini, Cleberton Diego; Medeiros, Rudinei Pinheiro; Corrêa, Luiz Liberato Costa; Freitas, Elisete Maria de; Johann, Liana (Acta Scientiarum. Biological Sciences, 2024)
One of the major setbacks in environmental restoration is how to promote the arrival of propagules in degraded areas, and this issue is intensified at sites without vegetation, where natural dispersal is limited. To overcome this issue, one of the methods employed is the use of artificial perches, intended for attracting seed-dispersing birds, providing perching sites, and thus, facilitating the formation of vegetation nuclei from the seeds that are excreted, regurgitated, or accidentally dropped. The aim of this study was to quantify and identify the birds that used the artificial perches in a degraded area on the margins of the Forqueta River, RS, Brazil, in order to evaluate their effectiveness as an ecological restoration method. Over one year, 11 bird species were observed to use the perches. Despite the presence of birds, there was no significant seed germination at the base of the perches. Absence of frugivorous species and adverse conditions of the soil might have contributed to this result. Previous studies showed diverging results on the effectiveness of artificial perches, indicating the need for considering several factors, such as availability of food resources and the presence of invasive species. The present study highlights the complexity of ecological processes involved in the restoration of degraded areas and the importance of adaptive approaches to reach effective results.